(untitled) (Journal of Medical & Health Sciences Review, 2025)
Typhoid fever is one of the serious blood stream infections in Pakistan with the most affected group of individuals are less than 10 years of age. Typhoid fever has a morbidity rate of over 21 million cases annually. Salmonella typhi, the causative agent of typhoid fever is primarily transmitted through oral-fecal route. Presence of toxins such as endotoxin (LPS), enterotoxin, and cytotoxin are all associated with virulence of S. typhi. Currently, laboratories diagnose typhoid fever through blood and stool cultures, which are considered the gold standard. Initially, the primary medications for treating typhoid were ampicillin, trimethoprim-sulfamethoxazole, and chloramphenicol. But the development of antimicrobial resistance with the multi-drug and extensively drug-resistant phenotype limited the treatment options. Resistance in S. typhi isolates more frequently associated with the acquisition of resistance genes, various types of plasmids specially those of Incompatibility (Inc) plasmids and chromosomal mutations. By ensuring access to immunizations, clean water, and proper hygiene practices, the likelihood of contracting typhoid can be reduced.